2007
DOI: 10.1300/j125v15n04_04
|View full text |Cite
|
Sign up to set email alerts
|

Building Community Capacity to Help Persons with Mental Illness

Abstract: In a time of crisis, persons with mental illness who encounter the police are often sent to jail or are involuntarily committed for psychiatric evaluation when mental health services are not readily available. To better serve these persons and the community, law enforcement and mental health professionals in one Iowa county joined together to ensure these individuals received the assessment and treatment needed. The results of a mixed methods program evaluation are detailed and suggest that the process to deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Stigma emerged as a noteworthy barrier to implementation and was part of a larger issue related to role clarity; this is consistent with the extant literature which suggests that on co-response teams roles, missions, and beliefs do not always align (Scott, 2000; Steadman et al, 2000; Hartford et al, 2006; Saunders & Marchik, 2007; Kisely et al, 2010; Rosenbaum, 2010; Department of Health and Human Services, Victoria, 2012; Kirst et al, 2015). Police in particular felt ostracized by fellow first responders.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Stigma emerged as a noteworthy barrier to implementation and was part of a larger issue related to role clarity; this is consistent with the extant literature which suggests that on co-response teams roles, missions, and beliefs do not always align (Scott, 2000; Steadman et al, 2000; Hartford et al, 2006; Saunders & Marchik, 2007; Kisely et al, 2010; Rosenbaum, 2010; Department of Health and Human Services, Victoria, 2012; Kirst et al, 2015). Police in particular felt ostracized by fellow first responders.…”
Section: Discussionsupporting
confidence: 81%
“…Despite these barriers, the findings offer several important facilitators to build out and implement first-responder co-response teams. For example, information sharing (or “triangulation”) was one of the most salient facilitators to both the MCAT in this study and other co-response teams (Lamb et al, 1995; Scott, 2000; Steadman et al, 2000; Ratansi, 2004; Baess, 2005; Hartford et al, 2006; Saunders & Marchik, 2007; Kisely et al, 2010; Rosenbaum, 2010; Department of Health and Human Services, Victoria, 2012; Kirst et al, 2015). New forms of data and lenses by which these data could be interpreted appeared to serve as a reinforcement mechanism that enabled team members to understand PMI experiences, track progress, and to try new solutions or those that were perceived to have previously worked.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Police officers often respond to mental health-related emergencies (Lamb, 1984), and studies suggest that PMI are more likely to be arrested than the general population (Borum et al, 1997; Charette et al, 2014; Fisher et al, 2011; Swartz & Lurigio, 2007; Teplin, 1984), which is explained in part by the lack of alternative response options following a mental health crisis (Borum, 2000; Engel & Silver, 2001; Hails & Borum, 2003; Lamb, 1984; Teplin, 1984). An emerging intervention to address mental health crises are co-responding police-mental health teams, also called co-response teams, mobile crisis teams, or crisis response teams (hereafter referred to as CRTs), which involve the pairing of a police officer with a social or medical service provider to provide initial emergency and/or follow-up response (Baess, 2005; Hay, 2014; Kirst et al, 2015; Kisely et al, 2010; Ratansi, 2004; Rosenbaum, 2010; Saunders & Marchik, 2007; Scott, 2000; Shapiro et al, 2015; Steadman et al, 2000; The Allen Consulting Group, 2012). There exists much variation in how CRTs are operationalized and implemented (Puntis et al, 2018), making it difficult to compare models; however, overall reported outcomes of CRTs are generally positive, with findings showing reductions in detainment and hospitalization of PMI and increased referral to community care services (Puntis et al, 2018; Shapiro et al, 2015; Watson et al, 2019).…”
mentioning
confidence: 99%